Attitudes towards Oral Health in Patients with Rheumatoid Arthritis: A Qualitative Study Nested within a Randomized Controlled Trial. (October 2019) - Serban, S.; Dietrich, T.; Lopez-Oliva, I.; de Pablo, P.; Raza, K.; Filer, A.; Chapple, I.L.C.; Hill, K.
Introduction: Patients with rheumatoid arthritis (RA) present a higher incidence and severity of periodontitis than the general population. Our study, Outcomes of Periodontal Treatment in Patients with Rheumatoid Arthritis (OPERA), was a randomized waiting-list controlled trial using mixed methods. Patients randomized to the intervention arm received intensive periodontal treatment, and those in the control arm received the same treatment with a 6-mo delay. Aim: The nested qualitative component aimed to explore patients' experiences and priorities concerning oral health and barriers and facilitators for trial participation. Methods: Using purposive sampling until thematic saturation was reached, we conducted 21 one-to-one semistructured interviews with randomized patients in either of the 2 treatment arms as well as with patients who did not consent for trial participation. Results: The patients described their experiences about RA, oral health, and study participation. Previous experiences with dental care professionals shaped patients' current perceptions about oral health and the place of oral health on their list of priorities compared with other conditions. Patients also highlighted some of the barriers and facilitators for study participation and for compliance with oral health maintenance. The patients, in the control arm, presented their views regarding the acceptable length of waiting time for the intervention. Conclusion: The associations between periodontal and systemic health are increasingly recognized by the literature. Our study provided an insight into RA patients' experiences and perceptions about oral health. It also highlighted some of the barriers and facilitators for participating in a periodontal interventional study for this group. We hope that our findings will support the design of larger interventional periodontal studies in patients with RA. The complex challenges faced by the burden of RA and the associated multimorbidities in this patient group might highlight opportunities to improve access to oral health services in this patient population. Knowledge Transfer Statement: This article provided insights into the experiences and perceptions of rheumatoid arthritis patients about their oral health to improve patient participation in a definitive clinical trial.